2020
DOI: 10.3390/genes11101136
|View full text |Cite
|
Sign up to set email alerts
|

MiR-4334-5p Facilitates Foot and Mouth Disease Virus Propagation by Suppressing Interferon Pathways via Direct Targeting ID1

Abstract: Emerging evidence indicates that the host microRNAs (miRNAs) are important intracellular regulators and play pivotal roles in intricate host-pathogen interaction networks. In our previous studies, ssc-microRNA-4334-5p (miR-4334-5p) was identified as a differentially expressed miRNA in microarray-based miRNAs profiling experiment, but whether miR-4334-5p regulates foot and mouth disease virus (FMDV) propagation is less understood. Here, we demonstrated that miR-4334-5p expression level was up-regulated shortly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 27 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…Accumulating evidences have shown that miRNAs play a crucial role in innate antiviral responses. For example, upon FMDV infection, miR-4334-5p regulates interferon (IFN) pathway by targeting ID1 ( 18 ). JEV exploits the miRNA regulatory mechanism that miR-155 inhibits the expression of IL-6 and TNF-α by targeting pellino 1 (PELI 1) to evade the host immunity ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidences have shown that miRNAs play a crucial role in innate antiviral responses. For example, upon FMDV infection, miR-4334-5p regulates interferon (IFN) pathway by targeting ID1 ( 18 ). JEV exploits the miRNA regulatory mechanism that miR-155 inhibits the expression of IL-6 and TNF-α by targeting pellino 1 (PELI 1) to evade the host immunity ( 19 ).…”
Section: Introductionmentioning
confidence: 99%